Circulating angiogenic biomolecules at rest and in response to upper-limb exercise in individuals with spinal cord injury. (March 2014) - Vasiliadis, Angelo V.; Zafeiridis, Andreas; Dipla, Konstantina; Galanis, Nikiforos; Chatzidimitriou, Dimitrios; Kyparos, Antonios; Nikolaidis, Michalis G.; Vrabas, Ioannis S.
<x content-type="archive" xml:space="preserve">Abstract</x> Objective Individuals with spinal cord injury (SCI) show structural and functional vascular maladaptations and muscle loss in their lower limbs. Angiogenic biomolecules play important roles in physiological and pathological angiogenesis, and are implicated in the maintenance of muscle mass. This study examined the responses of angiogenic molecules during upper-limb aerobic exercise in patients with SCI and in able-bodied (AB) individuals. Methods Eight SCI patients with thoracic lesions (T6–T12, ASIA A) and eight AB individuals performed an arm-cranking exercise for 30 minutes at 60% of their VO2max. Plasma concentrations of vascular endothelial growth factor (VEGF-A165), VEGF receptor 1 (sVEGFr-1), VEGF receptor 2 (sVEGFr-2), metalloproteinase 2 (MMP-2), and endostatin were measured at rest, after exercise, and at 1.5 and 3.0 hours during recovery. Results The two-way analysis of variance showed non-significant main effects of "group" and significant main effects of "time/exercise" for all angiogenic biomolecules examined (P < 0.01–0.001). The arm-cranking exercise significantly increased plasma concentrations of VEGF, sVEGFr-1, sVEGFr-2, MMP-2, and endostatin in both groups (P < 0.001–0.01). The magnitude of the increase was similar in both patients with SCI and AB individuals, as shown by the non-significant group × time interaction for all angiogenic parameters. Conclusions Upper-limb exercise (arm-cranking for 30 minutes at 60% of VO2max) is a sufficient stimulus to trigger a coordinated circulating angiogenic response in patients with SCI. The response of angiogenic molecules to upper-limb aerobic exercise in SCI appears relatively similar to that observed in AB individuals.